PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN POLA ASUH ORANG TUA TERHADAP KECERDASAN EMOSIONAL PESERTA DIDIK - Emawati Dewi Astuti; Subandi; Choirudin (STKIP Subang, 2026)
This study aims to analyze the effect of Islamic Religious Education learning and parenting styles on students’ emotional intelligence. This research employed a quantitative approach with a survey method. The population consisted of fifth-grade students of State Elementary School 22 Tumijajar, and the sampling technique used was total sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was conducted through prerequisite tests, namely normality and linearity tests, followed by hypothesis testing using multiple linear regression. The results showed that Islamic Religious Education learning has a significant effect on students’ emotional intelligence. Parenting styles also have a significant effect on emotional intelligence. Simultaneously, Islamic Religious Education learning and parenting styles have a significant influence on students’ emotional intelligence. These findings indicate that the synergy between school and family environments plays a crucial role in developing students’ emotional intelligence. Therefore, improving students’ emotional intelligence requires active roles from both teachers and parents in creating supportive learning and parenting environments, enabling students to develop not only cognitively but also emotionally and character-wise.